Sistem Pendukung Keputusan Penentuan Penerima Bantuan Bedah Rumah Menggunakan Metode Weighted Product Pada Kecamatan Borbor - Wasindo Hutahaean; Penda Sudarto Hasugian (Program Studi Teknik Komputer, Fakultas Teknik. Universitas Serambi Mekkah, 2021)
In rural areas there are still many residents 'houses that are unfit for habitation and this is due to the factor of the standard of living of people who are still living simply and have below average income, these conditions make many residents' houses unfit for habitation that need to be repaired through assistance Home renovation. The Weighted Product method can help in making decisions, but the calculation using the Weighted Product method only produces the largest value which will be selected as the best alternative. The design of decision-making for housing renovation assistance recipients at the Housing and Settlement Areas is based on criteria, namely Indonesian citizens, below average income, belonging to a family, owning or controlling land, not having a house or owning and living in an uninhabitable house using the Weighted Product method. Application design using the programming language PHP and MySQL